2014
DOI: 10.1080/13803395.2014.950636
|View full text |Cite
|
Sign up to set email alerts
|

Apathy is associated with white matter abnormalities in anterior, medial brain regions in persons with HIV infection

Abstract: Apathy is a relatively common psychiatric syndrome in HIV infection, but little is known about its neural correlates. In the present study, we examined the associations between apathy and diffusion tensor imaging (DTI) indices in key frontal white matter regions in the thalamocorticostriatal circuit that has been implicated in the expression of apathy. Nineteen participants with HIV infection and 19 demographically comparable seronegative comparison subjects completed the Apathy subscale of the Frontal Systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…In chronically HIV-infected groups, neural abnormalities in the nucleus accumbens and frontal cortex are associated with aspects of neurobehavioral disturbances (Kamat et al, 2014; Paul et al, 2005; Hoare et al, 2010). For example, our research group recently reported that higher apathy ratings in a group of chronically HIV-infected persons were associated with greater white matter abnormalities in the anterior corona radiata, genu, and orbital medial prefrontal cortex (Kamat et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In chronically HIV-infected groups, neural abnormalities in the nucleus accumbens and frontal cortex are associated with aspects of neurobehavioral disturbances (Kamat et al, 2014; Paul et al, 2005; Hoare et al, 2010). For example, our research group recently reported that higher apathy ratings in a group of chronically HIV-infected persons were associated with greater white matter abnormalities in the anterior corona radiata, genu, and orbital medial prefrontal cortex (Kamat et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, our research group recently reported that higher apathy ratings in a group of chronically HIV-infected persons were associated with greater white matter abnormalities in the anterior corona radiata, genu, and orbital medial prefrontal cortex (Kamat et al, 2014). The associations between white matter alterations and apathy were independent of depression and were stronger among participants with lower current CD4 cell counts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable attention has been directed to how white matter integrity and connectivity are factors in affective disorder (Bracht et al 2014;Nave and Ehrenreich 2014;Ota et al 2014) as well as in disorders where apathy may occur (Kamat et al 2014). Imposing injury either as an emotional trauma that occurs in PTSD or physical trauma related to acceleration/deceleration, blunt force or blast, white matter is vulnerable to injury, ranging from not apparent or minimal (Ilvesmaki et al 2014) to distinctly demonstrable microstructural abnormalities Waljas et al 2014).…”
Section: The Military Mtbi Conundrum and Svt/pvt Performancementioning
confidence: 98%